2017
DOI: 10.1177/2050640617703868
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, iron deficiency, active disease and female gender are independent risk factors for fatigue in patients with ulcerative colitis

Abstract: Probable psychiatric disorder, iron deficiency, active disease and female gender are independent risk factors for high fatigue in patients with ulcerative colitis. Low-grade immune activity does not seem to be the cause of fatigue among patients in deep remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 44 publications
(155 reference statements)
4
27
0
2
Order By: Relevance
“…In our study, women reported significantly higher anxiety testscores than men, which is corroborated by previous studies [46,47]. We did not find an association with ID or inflammation, although another study found that disorders such as anxiety or depression, disease activity, and gender are independent risk factors for fatigue in IBD [48].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, women reported significantly higher anxiety testscores than men, which is corroborated by previous studies [46,47]. We did not find an association with ID or inflammation, although another study found that disorders such as anxiety or depression, disease activity, and gender are independent risk factors for fatigue in IBD [48].…”
Section: Discussionsupporting
confidence: 92%
“…However, these studies did not determine endoscopic or biochemical remission, making it difficult to determine underlying IBD-related inflammatory burden accurately. One study (n = 288), in which fatigue was assessed during active disease and during deep remission, those in deep remission had no significant difference in immune markers, i.e., calprotectin, C-reactive protein (CRP), IL-17A, IL-6, IL-1b, IL-10, IL-8, TNFa, IL-13, IFN, IL-4, and IL-12, between those with fatigue and those without fatigue [9]. Thus, in quiescent disease, inflammation may not have a significant role in the pathogenesis of fatigue.…”
Section: Pro-inflammatory Statementioning
confidence: 99%
“…Thus, in quiescent disease, inflammation may not have a significant role in the pathogenesis of fatigue. However, active IBD with elevated cytokines, such as TNFa and IFNc, as well as elevated fecal calprotectin, correlates with the severity of fatigue [5,6,9,29,[32][33][34].…”
Section: Pro-inflammatory Statementioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal pain, diarrhea, weight reduction, and chronic fatigue are the main clinical characteristics of IBD, which significantly impair the quality of patients' life. Recent data have demonstrated that the chronic fatigue of patients is often closely associated with anemia [1, 2]. Although often neglected, anemia is known as the most frequent comorbidity of IBD [3], which may progress in the course of inflammatory response, intestinal bleeding, disorders of iron absorption [4, 5], vitamin B12 and folate deficiency, drug-related side effects, and hematologic diseases [68].…”
Section: Introductionmentioning
confidence: 99%